Alternatif Pembangkit Energi Listrik Menggunakan Prinsip Termoelektrik Generator - Sandy Angriawan Sasmita; Muhammad Taufiq Ramadhan; Mochamad Iqbal Kamal; Yohanes Dewanto (Universitas Tarumanagara, 2019)
Thermoelectric generator (TEG) has been used to produce electrical energy, the working principle of TEG, the temperature difference between two materials, will flow current, and produce a potential difference. This principle is known as the